Terapia com células-tronco mesenquimais de medula óssea e ácido hialurônico em calvária de coelhos - Ramalho, Renata Belmonte (2007)
The bone marrow s MSCs are already being used to repair craniofacial bones and regenerate oral tissues. The MSCs are cultivated and implanted in the affected tissue after that, they proliferate powerful responses. In order to reconstruct tissues from isolated and expanded cells in vitro, it would be advisable to implant these cells in a three-dimensional binding structure. In this structure, the cells can anchor, expand and discharge components which propitiate the tissue organization and the formation of a vascular net on the cell matrix. To evaluate the applications of the MSCs instilled in the Hyaluronic Acid Gel in the hypoplastic deformities of the membrane bone. We used three groups of rabbits. The groups were divided into a control group, a matrix group (H.A.) and research group. Bone marrow blood punctures of the femoral epifisis were carried out and the mononuclear cells were separated. Also, the culture of these cells was performed and after the cell trypinization they were incorporated to the Hyaluronic Gel and instilled into the bone deficiency. For the osteogenisis, the cuts were histologically colored with Masson Thrichrome. While assessing the morphological aspect of bone reparation, we observed that the repair seems to have followed regular patterns in the control group, but in the matrix group, this repair seems to have been stimulated by the presence of the Hyaluronic Acid Gel, which seems to promote the cellular proliferation and the group research better bone regeneration occurred. Inside the experimental condition and the achieved results in this research, we can conclude that in the research group, the morphological analyses of the tissues present in the bone deficiency indicate that this group seems to be more developed than the control and matrix group.